A new Marchand balun filter based on LTCC technology - Bai Ke (Dianzi Jishu Yingyong, 2019)
In this paper, a miniaturized distributed parameter balun filter based on Marchand balun structure is designed. The balun filter is based on low temperature cofired ceramic(LTCC) technology, the balun filter has maked full use of its multi-layer advantages and reduced the volume of the filter by LTCC multi-layer wiring. The structure of the balun filter adopted the spiral wide-side coupled stripline structure(SBCS), and the unique spiral cross-stacking structure, which effectively reduced the volume of the balun filter. The designed balun filter used dielectric material with relative dielectric constant of 9.8. Its size was only 2.0 mm×1.25 mm×0.95 mm. In the range of 1.805 GHz~2.17 GHz,the return loss was less than -12 dB, the amplitude imbalance was less than ±1.2 dB, and the phase imbalance was less than ±10°. It can completely meet the needs of today′s miniaturization of communication equipment.